Análise da aplicação do driver suplementar tipo POD para atenuação das oscilações eletromecânicas em complexos eólicos que utilizam a topologia DFIG - Gomes, Victor Lucas Sousa (2019)
Electric power systems are susceptible to frequent alterations in their operation conditions. These changes can provoke electromechanical oscillation modes which arise from the interaction between electromagnetic and mechanical system components. These oscillations, when poorly damped, can lead to restrictions on the stable operation of electric systems under transient conditions. They cause limitations in power transfers between busbars which may eventually lead to system collapse. Given these limitations, several devices have been developed in order to dampen those oscillations and thus increase the stability margin of such systems. The solution proposed here is concerned to the high penetration of wind generation in power systems, particularly with Double-Fed Induction Generators (DFIG topology) in wind parks. It has become appropriate to use this type of composition not only to supply power to the system, but also to promote auxiliary services to the power grid. Thus, this work aims to analyze the application of supplementary controllers to promote the attenuation of electromechanical oscillations referred to Power Oscillation Damping (POD) in the DFIG wind turbines. In order to adjust the variables of the supplementary controllers it was chosen the residue method. It can be concluded from the simulation results obtained with the software MATLAB that the adjustments performed by the residue method were able to satisfactorily dampen the proposed oscillation modes.